Penerapan Penerapan Zahir Accounting versi 5.1 Pada Laporan Keuangan Perusahaan Dagang EJ. Endik Jaya Bogor: Laporan Keuangan Perusahaan Dagang - Siregar, Juarni; Revita, Maria Lapriska Dian Ela; Hibono, Leonita (Sistem Informasi Akuntansi Kampu Kabupaten Karawang, 2021)
The era of the Industrial revolution 4.0, all using internet connecting, especially in the field of hardware technology in the form of computers and software technology in the form of applications. The existence of computers and applications can make data processing faster and more accurate and saves storage space in archiving. One of them is in processing financial data in various companies. At present there are still many companies that manage their financial data manually, including EJ. Endik Jaya. Weaknesses in the processing of financial data manually will be vulnerable to errors in the financial recording process, resulting in inaccurate reports. Therefore, by direct observation on company locations and interviews with EJ owners. Endik Jaya the author collects the evidence of the transaction and observes the processing of the company's financial data, to then apply it to Zahir Accounting Version 5.1. In addition, the author also uses the literature study method by reading books containing Zahir Accounting Version 5.1. It is expected that with the application of this application the process of financial records on EJ. Endik Jaya is becoming more effective and efficient, and produces financial reports that are fast, precise and accurate.